2010
DOI: 10.1177/0264619609359753
|View full text |Cite
|
Sign up to set email alerts
|

Horatio audio-describes Shakespeare’s Hamlet

Abstract: Audio description (AD) has been introduced as one solution for providing people who are blind or have low vision with access to live theatre, film and television content. However, there is little research to inform the process, user preferences and presentation style. We present a study of a single live audio-described performance of Hart House Theatre’s production of Hamlet in Toronto, Ontario. Unlike conventional description, the AD was designed in cooperation with the creative team to fit with the producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…In the field of media accessibility, subtitling for the Deaf and Hard-of-Hearing has attracted considerable attention (Romero-Fresco, 2016) and there is also extensive research on audio description (AD). The reception of AD has been studied when applied to the theatre (Udo et al, 2010), to fashion shows (Udo & Fels, 2009), opera (Cabeza-Cáceres, 2010;Cabeza-Cáceres & Matamala, 2008;Eardley-Weaver, 2014;Orero, 2007; and cinema (Fresno Cañada, 2014;Cabeza-Cáceres, 2013;Fernández-Torné & Matamala, 2016;Szarkowska, 2011). Studies in this field have focused on many aspects, such as information recall (Fresno Cañada, 2014) or user comprehension and enjoyment (Cabeza-Cáceres, 2013) when faced with diverging AD strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of media accessibility, subtitling for the Deaf and Hard-of-Hearing has attracted considerable attention (Romero-Fresco, 2016) and there is also extensive research on audio description (AD). The reception of AD has been studied when applied to the theatre (Udo et al, 2010), to fashion shows (Udo & Fels, 2009), opera (Cabeza-Cáceres, 2010;Cabeza-Cáceres & Matamala, 2008;Eardley-Weaver, 2014;Orero, 2007; and cinema (Fresno Cañada, 2014;Cabeza-Cáceres, 2013;Fernández-Torné & Matamala, 2016;Szarkowska, 2011). Studies in this field have focused on many aspects, such as information recall (Fresno Cañada, 2014) or user comprehension and enjoyment (Cabeza-Cáceres, 2013) when faced with diverging AD strategies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Stangl et al [110] and Bodi et al [6] investigated the viability of providing video access through interactive visual question answering, reinforcing the importance of BLV users having agency in the process of making videos accessible. Others explored the impact of changing the tone or style of verbal descriptions for select video types, finding that alternative AD styles were engaging for BLV users [30,59,121,125]. Additionally, Romero-Fresco et al [98] conducted a preliminary study on the efficacy of audio introductions for providing additional detail to described films.…”
Section: Video Accessibilitymentioning
confidence: 99%
“…6.1.6 Tone and Style of Approach (categorical): excited, sad, judgmental, first-person perspective, cartoonish, etc. While most existing AD is generally presented in a neutral, third-person tone [28,70], researchers have found that changing the tone or style of verbal description presentation can improve viewers' immersion in a video [30,59,121,125]. We explored how this could extend to a variety of different scenarios.…”
Section: Defining the Design Space For Video Accessibilitymentioning
confidence: 99%
“…Komentavimo procesas ir stiliai yra dar mažai ištirti, bet pastaruoju metu atliekami įvairūs tyrimai: pvz., buvo išnagrinėtas spektaklio Hamletas, vykusio Toronte (Kanadoje), Hart House'o teatre, garsinis komentaras. Garsinio komentaro tekstas buvo parengtas iš anksto, laikantis Shakespeare'o stiliaus ir ritmikos (jambinio pentametro), ir buvo sakomas Horacijaus vardu (Udo, Acevedo, Fels 2010). Auditorija palankiai įvertino ir komentarą, ir spektaklį, nes, autorių teigimu, viskas buvo atlikta novatoriškai.…”
Section: Kitų Vertimų Regos Neįgaliesiems Ypatybėsunclassified